Restoring Esthetics after Anterior Tooth Loss for a Five-Year-Old Child: Natural Tooth Pontic Fiber Reinforced Prosthesis - Dhirja Goel; Gaurav Kumar Goel (Case Reports in Dentistry)
The loss of anterior teeth can be hurtful to the patient both psychologically and socially. As the children are becoming more aware these days, they have also become conscious about their looks. Early loss of deciduous anterior teeth has a psychological effect on many children. In such young patients, paper replacement of the teeth can minimize these concerns. Many approaches have been described for this temporary replacement. This article describes the technique to use extracted natural teeth as pontics bonded to adjacent teeth with fiber reinforced resin. A fiber reinforced temporary replacement of missing teeth provides adequate strength and esthetic requirements in such cases.